Endovascular Thrombectomy for Large Core Ischemic Stroke: A Review of Recent Evidence - Schwartz, Zachary L.; Jones, Jesse G. (Seminars in Interventional Radiology, 2025)
Treatments for acute ischemic stroke have rapidly evolved in recent decades. Endovascular thrombectomy (EVT) has joined intravenous thrombolysis as the standard of care for ischemic stroke patients meeting certain criteria. The application of endovascular techniques in subgroups of ischemic stroke patients is a topic of active research. Stroke patients presenting with a large volume ischemic core have historically been inadequately studied. Multiple recent trials describe the results of applying EVT to this subgroup. Some trials show that EVT offers benefit for patients with large core ischemic stroke, though this result is not uniform. Though meta-analyses exist, heterogeneity in these studies complicates their comparison. Recent evidence challenges historical notions that thrombectomy in this subgroup carries increased risk of symptomatic intracranial hemorrhage.
Keywords: stroke; large core ischemia; endovascular thrombectomy; neurointervention